Perwujudan Sila ke-5 Pancasila bagi Penyandang Disabilitas dalam Mendapatkan Hak-Hak Fundamental berdasarkan Undang-Undang Nomor 8 Tahun 2016 - Riskanita, Dinda; Sulistyowati, Andita; Nugroho, Dendy Prasetyo (Legal Standing : Jurnal Ilmu Hukum, 2025)
The 5th principle of Pancasila contains the principle of justice in various aspects of life without discrimination against anyone, including people with disabilities. This principle emphasizes that every citizen, including people with disabilities, has the right to receive equal treatment, access to basic rights, and equal opportunities in community, national and state life. Through Law Number 8 of 2016 concerning Penyandang Disabilitas, as a form of government responsibility in creating policies that favor people with disabilities and eliminate discrimination. This study aims to analyze and examine the manifestation of the principle of social justice in Pancasila, especially regarding the fulfillment of basic rights for people with disabilities. The main focus of this study is to explore the extent to which the application of the principle of social justice in Pancasila contributes to equality, protection, and fulfillment of the basic rights of people with disabilities in various aspects of life. This research is a normative legal research with a statue approach, by examining secondary legal materials using the library research method, where the research will answer the problem by using supporting legal theories through literature studies. The results of this study explain that the 5th principle of Pancasila demands social justice in fulfilling basic rights for people with disabilities, namely in the fields of education, employment, health, accessibility, socio-political participation, legal protection and social security. This study emphasizes the importance of ensuring that people with disabilities are not only respected, but also given equal opportunities to enjoy their basic rights in all aspects of life. Pancasila, as the basis of the state, emphasizes that social justice for people with disabilities is the state's obligation to realize it through policies and real actions. Law Number 8 of 2016 is a concrete form of government commitment in ensuring the fulfillment of the basic rights of people with disabilities.